2017
DOI: 10.1016/j.margeo.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A depositional model for seismo-turbidites in confined basins based on Ionian Sea deposits

Abstract: This study investigates Ionian Sea seismo-turbidite (ST) deposits that we interpret to be triggered by major historic earthquakes and tsunamis in the Calabrian Arc. ST beds can be correlated with the AD 1908 Mw 7.24 Messina, AD 1693 Mw 7.41 Catania, and AD 1169 Mw 6.6 Eastern Sicily earthquakes while two previously unknown turbidites might have been generated by the AD 1818 Mw 6.23 Catania and AD 1542 Mw 6.77 Siracusa earthquakes.\ud Textural, micropaleontological, geochemical and mineralogical signatures of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 80 publications
(162 reference statements)
5
46
0
Order By: Relevance
“…Previous studies on the Holocene showed that the gravity‐driven deposits have a co‐seismic origin (Polonia et al, a, b, ; San Pedro et al, ). The large majority of the seismo‐turbidite deposits present amalgamated or stacked beds, characteristic of the deposition by multiple quasi‐synchronous flows (Gutiérrez‐Pastor et al, ; Migeon et al, ; Nelson et al, ; Polonia et al, ) and the presence of liquefaction figures and faults should be the witnesses of a co‐seismic origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the Holocene showed that the gravity‐driven deposits have a co‐seismic origin (Polonia et al, a, b, ; San Pedro et al, ). The large majority of the seismo‐turbidite deposits present amalgamated or stacked beds, characteristic of the deposition by multiple quasi‐synchronous flows (Gutiérrez‐Pastor et al, ; Migeon et al, ; Nelson et al, ; Polonia et al, ) and the presence of liquefaction figures and faults should be the witnesses of a co‐seismic origin.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of these two accretionary wedges over a million years scale (Coy et al, ; Dewey & Sengör, ; Gallais et al, ; van Dijk & Scheepers, ; Truffert, ) as well as their morphology and present day functioning have been widely studied (D'Agostino et al, ; Gutscher et al, ; Huguen et al, ; Kreemer & Chamot‐Rooke, ; Polonia et al, ; Tortorici et al, ). For the last thousand years, Polonia et al (b, ) has focused initially on the Holocene's palaeoseismology based on turbidite record and, more recently, studies have been extended to the last 60 ka (Köng et al, ). Between these two time scales (million years and the last thousand years) few studies deal with the turbidite record in active margin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This plateau is, however, dissected by long normal and strike-slip fault zones mostly striking NW-SE. The inner plateau is characterized by chaotic units (Rossi and Sartori, 1981) and many mud volcanoes (Praeg et al, 2009;Ceramicola et al, 2014;Gutscher et al, 2017;Loher et al, 2018) including the BMV that is studied in this work.…”
Section: Geological Settingmentioning
confidence: 99%
“…Many mud volcanoes occur on active accretionarysedimentary prisms (Cita, 1981;Kopf, 2002;Panieri et al, 2013;Ceramicola et al, 2014), where their degassing activity is at least in part connected with active compression and associated faulting and fracturing (Camerlenghi et al, 1995;Kopf, 2002;Chamot-Rooke et al, 2005;Mazzini et al, 2007;Panieri et al, 2013). It is also noteworthy that, in these active tectonic settings, the longevity of mud volcanoes may even exceed 1 Ma (Cita et al, 1989;Camerlenghi et al, 1992Camerlenghi et al, , 1995Robertson, 1996;Kopf et al, 1998;Praeg et al, 2009;Somoza et al, 2012). All together the known submarine mud volcanoes release about 27 Mt methane a −1 (plus other gases ;Milkov, 2004;Etiope and Milkov, 2004).…”
mentioning
confidence: 99%